L’intuition dans l’apprentissage et l’emploi d’une langue étrangère : pourquoi la notion est-elle importante ? - Piegzik, Wioletta (Moderna Språk, 2024)
The article discusses properties and the role of intuition in learning and using a foreign language. While intuition plays a crucial role in various cognitive processes, its specific implications in linguistics and foreign language pedagogy remain incompletely understood. The first part presents the main theses and research findings on intuition in linguistics (Chomsky, Guillaume, Benveniste, Langacker) and foreign language didactics (Krashen, Ellis, Oxford, DeKeyser, etc.). The second part outlines an empirical study of linguistic behaviours based on intuition. The study focuses on the evaluative function of intuition linked to the rapid judgment of the grammatical correctness of sentences and the compensation function, which involves the immediate inference of the meaning of unknown lexical units from the context. The study results, conducted with 102 students of French as a foreign language, show that at the level of intuitive behaviours concerning the morphological and syntactic subsystems, their linguistic reactions, fast and unconscious behaviours, are characterised by more significant correction than conscious behaviours. On the other hand, as far as the intuitive behaviour related to the lexical-semantic subsystem is concerned, better results are generated by longer reaction times. The study also demonstrated that intuition supports not only native users, but also foreign langue learners at intermediate level of proficiency.